The Fruitghurt Formulations are Combination of Red Guava and Pineapple Juice by using the Encapsulation Method, as an Alternative Source of Vitamin C (Jurnal Online Pertanian Tropik, 2023)
Fruitghurt is a product of fermented fruit juice using Lactobacillus bulgaricus and Streptococcus thermophillus bacteria. This research was conducted of developing fruitghurt products that contain vitamin C with a combination of red guava and pineapple juice. The research method was carried out using a factorial completely randomized design method which consisted of two factors. Factor I: combination of red guava and pineapple juice: JN1=120%:80%; JN2=130%:70%, JN3=140%:60%, JN4=150%:50%. Factor II: drying time L1=1 hour, L2=2 hours, L3=3 hours, L4=4 hours. The results showed that the concentration of red guava and pineapple juice had a very significant effect (p